2001
DOI: 10.1038/sj.mp.4000954
|View full text |Cite
|
Sign up to set email alerts
|

Increase in cell proliferation in dentate gyrus following fluoxetine treatment in rat maternal separation model

Abstract: Fluoxetine treatment during maternal separation enhances cell proliferation in the dentate gyrus. BrdU-immunostaining and methyl green counterstaining were done on sections obtained one day after the last day of the injections from each group; pups kept with their mothers (a) and pups with maternal separation (b), which have received daily injections of BrdU (50 mg kg −1 ) and saline, and fluoxetine-treated pups with maternal separation (c) which have received daily injections of BrdU (50 mg kg −1 ) and fluoxe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…This apparent hippocampal vulnerability to ELS is in line with a growing body of evidence which indicates that, as an important mediator in the stress response, the hippocampus is especially susceptible to the deleterious effects of insults such as ELS. The impacts of stress in the hippocampus can manifest as structural abnormalities, decreased plasticity, and altered neurogenesis, all of which may play a role in the later manifestation of neuropathology (Lee et al, 2001;Hanson et al, 2015;Hoeijmakers et al, 2015;Lajud and Torner, 2015). Furthermore, hippocampal damage resulting from the accumulation of abnormally aggregated proteins, which can occur as a result of impairing the process of proteostasis, is a hallmark of several neurodegenerative diseases (Moodley and Chan, 2014;Heckmann et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This apparent hippocampal vulnerability to ELS is in line with a growing body of evidence which indicates that, as an important mediator in the stress response, the hippocampus is especially susceptible to the deleterious effects of insults such as ELS. The impacts of stress in the hippocampus can manifest as structural abnormalities, decreased plasticity, and altered neurogenesis, all of which may play a role in the later manifestation of neuropathology (Lee et al, 2001;Hanson et al, 2015;Hoeijmakers et al, 2015;Lajud and Torner, 2015). Furthermore, hippocampal damage resulting from the accumulation of abnormally aggregated proteins, which can occur as a result of impairing the process of proteostasis, is a hallmark of several neurodegenerative diseases (Moodley and Chan, 2014;Heckmann et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…6) Moreover, several reports suggest that antidepressants promote cell proliferation in the dentate gyrus by antiapoptotic and neuroprotective activities. 23,24) Therefore, these effects of RA may result in the increase of cell proliferation in the dentate gyrus. However, it remains to be unclear why increase in BrdU-positive cells in the dentate gyrus shows an antidepressant-like effect, and further studies are needed to address the issue.…”
Section: Discussionmentioning
confidence: 99%
“…One study of rats showed fluoxetine exposure protected rat offspring from the effects of pregnancy stress on adolescent outcomes for both depressive symptoms, as measured by the Forced Swim Test, and increased hippocampal neurogenesis [156]. A second study showed that fluoxetine exposure in rat pups separated from their mothers protected against cell apoptosis of the dentate gyrus of the hippocampus [157]. A study of human neonates showed early speech perception was more advanced in those exposed to selective serotonin reuptake inhibitors than those exposed to controls [158].…”
Section: Positive Effects Of Intrauterine Exposuresmentioning
confidence: 99%